Extreme iron cycling in a coastal lake-lagoon system driven by interactions between climate and entrance management - Scott G. Johnston; Thor Aaso; Damien T. Maher; Edward D. Burton; Mitchell Call; Mathew Birch; John Schmidt; Angus Ferguson (Science of The Total Environment, 2024)

Alkalinity export to the ocean is a major carbon sequestration mechanism in a macrotidal saltmarsh - Yvonne Y.Y. Yau; Pei Xin; Xiaogang Chen; Lucheng Zhan; Mitchell Call; Stephen R. Conrad; Christian J. Sanders; Linwei Li; Jinzhou Du; Isaac R. Santos (Limnology and Oceanography, 2022)
Saltmarshes are a blue carbon ecosystem accumulating large quantities of organic carbon in sediments. Some of this carbon can be transformed into dissolved inorganic carbon (DIC) and methane (CH 4 ) that may eventually be exported to the ocean or atmosphere. Although extensive studies have quantified specific components of the carbon budget such as carbon burial, limited attention has been given to pore‐water‐derived carbon and total alkalinity (TA) exports to the ocean. Here, we quantified lateral exports to the ocean (outwelling) of 202 ± 160 and 78 ± 75 mmol m −2 d −1 of DIC and TA, respectively. The TA : DIC concentration ratio in the creek waters was ~ 1, implying TA production from anaerobic mineralization in sediments. The lateral TA exports were comparable to the local (94 ± 48 mmol m −2 d −1 ) and national (~ 50 mmol m −2 d −1 ) organic carbon burial. High TA exports could locally increase the ocean buffering capacity and contribute bicarbonate to the coastal ocean, acting as a long‐term carbon storage. Pore water traced by radon contributed 28–37% and 58–69% of DIC and TA exports. Separating the two major DIC components (i.e., CO 2 emissions and alkalinity exports) is essential to resolve the carbon sequestration potential from saltmarshes. Here, dissolved CO 2 emissions to the atmosphere accounted for 3–5% of total DIC outwelling. CH 4 emissions played a minor role offsetting around 0.3 to 6% of the carbon sequestration. Overall, we demonstrate that alkalinity export into the ocean can be an overlooked carbon sequestration pathway in saltmarshes at rates comparable to carbon burial.

The mangrove CO 2 pump: Tidally driven pore‐water exchange - Xiaogang Chen; Isaac R. Santos; Mitchell Call; Gloria M. S. Reithmaier; Damien Maher; Ceylena Holloway; Praktan D. Wadnerkar; Paula Gómez‐Álvarez; Christian J. Sanders; Ling Li (Limnology and Oceanography, 2021)
Atmospheric carbon dioxide (CO 2 ) is fixed by mangrove vegetation and stored in its biomass and sediments. Part of the sediment carbon can be exported to coastal waters via tidally driven pore‐water exchange. Here, we quantify pore water‐derived dissolved CO 2 export using in situ, high‐resolution observations of 222 Rn and CO 2 over a spring‐neap tidal cycle in a mangrove‐fringed estuary (Coffs Creek, Australia). 222 Rn‐derived pore‐water exchange rates were 11.5–34.9 cm d −1 (23.0 ± 6.7) over 30 tidal cycles. Pore‐water exchange released CO 2 from intertidal sediment at rates of 61–213 (136 ± 43) mmol m −2 d −1 . This is equivalent to ~ 94% of the total CO 2 input into the estuary and approximately two times of the water‐atmosphere CO 2 emission. These observations reveal that tidal pumping is a major regulator of both mangrove pore‐water exchange and associated dissolved CO 2 export to the ocean. Combining our estimates with literature data, a first‐order global pore water‐derived dissolved CO 2 export from mangroves was estimated to be 83 ± 50 Tg C yr −1 . This is higher than an earlier estimates of global mangrove CO 2 emissions to the atmosphere (34.1 ± 5.4 Tg C yr −1 ) and carbon burial in sediments (18.4–34.4 Tg C yr −1 ), implying that pore water‐derived CO 2 escapes to the atmosphere within and beyond mangrove waters. Overall, CO 2 ‐rich pore water seems to be a widespread, important pathway of CO 2 into mangrove‐dominated estuaries and should be considered in mangrove carbon assessments in the context of global climate change and blue carbon.

Coastal carbon cycle changes following mangrove loss - James Z. Sippo; Christian J. Sanders; Isaac R. Santos; Luke C. Jeffrey; Mitchell Call; Yota Harada; Kylie Maguire; Dylan Brown; Stephen R. Conrad; Damien T. Maher (Limnology and Oceanography, 2020)
Global mangrove loss is occurring from deforestation and extreme climatic events, but changes to the coastal carbon cycle following mangrove mortality and/or loss are not well understood. In 2015/2016, a massive climate‐driven mangrove dieback event occurred over ~ 1000 km of Australian coastline. To assess carbon loss following mortality, carbon fluxes in adjacent living and dead forest areas were compared 8 and 20 months postforest dieback. Dead areas experienced an increase in soil CO 2 efflux by ~ 189%, and a decrease in oceanic dissolved inorganic carbon (DIC) outwelling of ~ 50% relative to living areas. DIC outwelling (predominantly carbonate alkalinity) and soil CO 2 efflux accounted for 81% and 16% of losses from the living forest, in comparison to 51% and 47%, respectively, from the dead forest. The dieback drove a shift from a dominance of oceanic carbon outwelling to increased atmospheric CO 2 emissions and decreased alkalinity exports. This shift was likely driven by increased oxygen sediment permeation and the loss of mangrove net primary productivity. Combining our new observations with literature data, we found a logarithmic relationship between soil carbon loss and time since mangrove loss. Using this relationship, we estimate ongoing global carbon losses from historical mangrove deforestation and dieback could be 13.7 ± 9.4 Tg C yr −1 , which is eightfold higher than previous estimates and offsets global mangrove carbon burial by ~ 60%. Even if no future deforestation occurred, we estimate ongoing carbon losses to the atmosphere and ocean from current global mangrove losses of 27 Tg C over the next 30 yr.

Hydrological Versus Biological Drivers of Nutrient and Carbon Dioxide Dynamics in a Coastal Lagoon - Damien T. Maher; Mitchell Call; Paul Macklin; Jackie R. Webb; Isaac R. Santos (Estuaries and Coasts, 2019)